Islam dan Nilai-Nilai Universal di Era Global: Menyatukan Identitas dan Kemanusiaan - Nur Amanah; Muhammad Tegar Ramadhan; Mukmin Mukmin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Globalization has brought profound changes to social and cultural structures, resulting in identity tension, growing polarization, and the weakening of humanitarian values. This study aims to examine the urgency of reconstructing universal Islamic values as a foundation for unifying identity and humanity in the global era. Employing a library research method, this study analyzes relevant books as well as national and international journal articles using thematic content analysis. The findings reveal that universal Islamic principles, including justice (al-‘adl), compassion (rahmah), respect for human dignity, tolerance, and balance, function as ethical guidelines capable of responding to contemporary global challenges. Furthermore, the concept of religious moderation (wasathiyah) is identified as a strategic middle path that harmonizes religious identity with global citizenship. The study also emphasizes the importance of digital religious literacy in countering misinformation and extremism. Ultimately, universal Islamic values must be translated from normative discourse into practical implementation within education, public policy, and social engagement to foster a peaceful and inclusive global civilization.   Keywords: Universal Islamic Values, Global Identity, Religious Moderation.